Community Structure, Conservation Status, and Functional Groups of Bird Species in Mbeya Range Forests, Tanzania - Ojija, Fredrick; Manyanza, Ndaki Marco (Journal of Basic & Applied Sciences, 2022)
The Mbeya range forest reserves (MRFRs) of the southern highland of Tanzania are an important hotspot for biodiversity conservation. However, its avian biodiversity has hardly ever been studied. Thus, for the first time, this study presents the inventory of bird species from MRFRs, demonstrating community structure, functional group, and conservation status. The study was carried out in four forest areas (i.e., Idugumbi, Kawetire, Mount Loleza, and Muvwa) within the MRFRs. The bird survey was carried out monthly between March 2018 and June 2018. Standardised line and point counts, as well as mist netting, were used to collect data. A total of 1052 individual birds, representing 41 species and 22 families, were recorded. Relative abundance, Shannon and Simpson species diversity, and species richness were high in Idugumbi forest and lowest in Kawetire forest. Species diversity differed significantly between the four forest areas. Moreover, Idugumbi and Muvwa had relatively low species composition dissimilarity compared to other forest areas. Different bird functional groups, i.e., insectivores, granivores, nectarivores, carnivores, frugivores, or combinations of these, were recorded in MRFRs. The insectivores were twice as abundant as granivores and nectarivores. The multi–layered vegetation structure of native plants in the Idugumbi forest appears to benefit and contribute to bird communities. The study reveals that MRFRs are an important hotspot for bird species that require ecological monitoring and protection. As a result, appropriate land–use practices near MRFRs should be followed to ensure long–term avian conservation.